The The Impact of the Discovery Learning Model Supported by Pop-Up Book Media on Fourth-Grade Elementary School Students' Cognitive Learning Outcomes in Animal Metamorphosis - Murdiani, Eka; Rohan, Gregorius; Rosmaiyadi; Sumarli (LPPM Universitas PGRI Semarang, 2025)
This study aimed to find out; (1) To find out whether or not there is a difference in students' cognitive learning outcomes between classes that use the Discovery Learning model assisted by Pop-Up Book learning media and classes that use the direct learning model; (2) To determine the influence of the Discovery Learning model assisted by Pop-Up Book learning media on the learning outcomes of the cognitive domain of fourth-grade elementary school students on animal metamorphosis materials; (3) To describe students' responses to the application of the Discovery Learning model Assisted by Pop-Up Book media. The type of research used in this study is quantitative research. This research was conducted at SDN 62 Singkawang. The subject of the study was a fourth-grade elementary school student. The data collection techniques used are test techniques and non-test techniques. The data collection instruments used are question sheets and student response questionnaires. The results of this study show that 1) There is a significant difference in the learning outcomes of the cognitive domain of fourth-grade students between classes that use the Discovery Learning model assisted by Pop-Up Book media and classes that use the direct learning model; 2) The Discovery Learning model assisted by Pop-Up Book media has a high influence on the cognitive learning outcomes of fourth grade students in science learning at SDN 62 Singkawang; 3) Positive student responses to the application of the Discovery Learning model assisted by Pop-Up Book media.